Cultivating Morals in the Formation of Behavior Student at MTSN 1 Bengkulu City - Satria, Irwan (Madania: Jurnal Kajian Keislaman, 2022)
This study aims to determine the implementation of student moral formation at MTsN 1 Bengkulu City. This research uses a qualitative approach by examining social phenomena in an atmosphere that occurs naturally. The researcher acts as an observer in the formation of morals at MTsN 1 Bengkulu City. The research instrument used was data collection techniques, interviews, and observations in learning to read the Koran, as well as through observation, interviews, and documentation. Based on the results of the interviews, it was found that the formation of morals towards oneself at MTsN 1 Bengkulu City was good. This can be seen in the formation of morals by reciting the Quran before entering class, praying dhuha in the congregation, making disciplinary rules, and punishing those who violate it. The formation of morals towards parents is done by making rules that have made students have good morals, plus the role of parents as a factor that can be used as a step in improving student morals. The formation of morals towards friends/friends produces good morals that can be used in social life after they enter society. The formation of morals towards teachers needs to be improved with better steps because students will respect teachers with good morals. The formation of morals towards older and younger people states that MTsN 1 Bengkulu City has taught its students always to respect elders. The formation of morals towards the environment / surrounding environment proves that MTsN 1 Bengkulu City has taken reasonable steps in forming morals at school. Penelitian ini bertujuan untuk mengetahui implementasi pembentukan moral siswa di MTsN 1 Kota Bengkulu. Penelitian ini menggunakan pendekatan kualitatif dengan cara mengkaji fenomena sosial dalam suasana yang berlangsung secara natural. Peneliti berperan sebagai pemerhati dalam pembentukan akhlak di MTsN 1 Kota Bengkulu. Instrumen penelitian yang digunakan adalah dengan menggunakan teknik pengumpulan data, wawancara, dan observasi dalam proses pembelajaran membaca Alquran, serta melalui observasi, wawancara dan dokumentasi. Berdasarkan hasil wawancara didapatkan bahwa pembentukan akhlak terhadap diri sendiri di MTsN 1 Kota Bengkulu sudah baik. Hal ini terlihat dari pembentukan akhlak dengan mengaji sebelum masuk kelas, sholat dhuha berjamaah, membuat aturan disiplin , memberikan hukuman bagi yang melanggarnya. Pembinaan akhlak terhadap orang tua dilakukan dengan membuat peraturan yang telah menjadikan siswa memiliki akhlak yang baik ditambah peran orang tua sebagai faktor yang dapat dijadikan sebagai langkah dalam meningkatkan akhlak siswa. Pembentukan akhlak terhadap teman/sahabat menghasilkan akhlak yang baik yang dapat digunakan dalam kehidupan bermasyarakat setelah mereka memasuki masyarakat. Pembinaan akhlak terhadap guru perlu ditingkatkan dengan langkah-langkah yang lebih baik, karena dengan akhlak yang baik siswa akan menghormati guru. Pembentukan akhlak terhadap yang lebih tua dan lebih muda menyatakan bahwa MTsN 1 Kota Bengkulu telah mengajarkan kepada siswanya untuk selalu menghormati orang yang lebih tua. Pembentukan akhlak terhadap lingkungan/lingkungan sekitar membuktikan bahwa MTsN 1 Kota Bengkulu telah mengambil langkah yang baik dalam pembentukan akhlak di sekolah.